resolva a equação pelo método da substituição
![x - y = 3 \\ 2x + y = 9 x - y = 3 \\ 2x + y = 9](https://tex.z-dn.net/?f=x+-+y+%3D+3+%5C%5C+2x+%2B+y+%3D+9)
Soluções para a tarefa
Respondido por
2
Explicação passo-a-passo:
.
{x-y=3
{2x+y=9
{x-y=3
{y=9-2x
x-y=3
x-(9-2x)=3
x-9+2x=3
3x-9=3
3x=3+9
3x=12
x=12/3
x=4
y=9-2x
y=9-2×4
y=9-8
y=1
Perguntas interessantes
Geografia,
7 meses atrás
Matemática,
7 meses atrás
História,
7 meses atrás
Química,
9 meses atrás
História,
9 meses atrás
Matemática,
1 ano atrás
Contabilidade,
1 ano atrás